1999
DOI: 10.1007/s11746-999-0186-0
|View full text |Cite
|
Sign up to set email alerts
|

Soybean drying in fluidized bed. effect on the hydratable and nonhydratable phosphatide concentration in crude and degummed crude oil

Abstract: The content of nonhydratable phosphatides in soybean crude oil is increased by phospholipase D activity during the oil-making process. Enzyme inhibition would allow to minimize them. Recently harvested soybeans with high moisture levels require adequate drying to store safely. Simultaneous soybean drying and phospholipase D inactivation in a single operation when applying a thermal treatment by the fluidized-bed technique was evaluated. The process conditions for performing the drying and a complete enzyme inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…Discrepancies in the values of PLD activity (PLDA) arise from comparing the results obtained by List et al (1990List et al ( , 1992 and by Tosi et al (1999). The PLDA found by Tosi et al was 150 times the PLDA found by List et al In their works, List et al (1990, 1992 applied the method of extracting the enzyme from the soybean original matrix according to a modification of the method proposed by Nakayama et al (1981) to extract the PLD from white cabbage.…”
Section: Soybean Phospholipase D Activity Determination a Comparisonmentioning
confidence: 99%
See 2 more Smart Citations
“…Discrepancies in the values of PLD activity (PLDA) arise from comparing the results obtained by List et al (1990List et al ( , 1992 and by Tosi et al (1999). The PLDA found by Tosi et al was 150 times the PLDA found by List et al In their works, List et al (1990, 1992 applied the method of extracting the enzyme from the soybean original matrix according to a modification of the method proposed by Nakayama et al (1981) to extract the PLD from white cabbage.…”
Section: Soybean Phospholipase D Activity Determination a Comparisonmentioning
confidence: 99%
“…On the other hand, Tosi et al (1999) used a method based on the action of the PLD, contained in the soybean original matrix, by mixing up milled soybean with soybean lecithin as substrate. Both authors used the same 270 GRASAS Y ACEITES, 58 (3), JULIO-SEPTIEMBRE, 270-274, 2007, ISSN: PSOYBEAN PHOSPHOLIPASE D ACTIVITY DETERMINATION.…”
Section: Soybean Phospholipase D Activity Determination a Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…For the reference oil, a residual phosphorus content of 150 ppm was assumed after water degumming and the phosphatide composition of the NHP is in accordance with [10]. The expander treatment of soya [15,16] and the drying of soya beans in a fluidised bed [17] also lead to more phosphatides in the crude oil but less residual phosphatides in water-degummed soya bean oil and similar observations have been made for rapeseed oil [18].…”
Section: Introductionmentioning
confidence: 82%
“…Tosi et al. (1999) reported the decrease of nonhydratable phosphatides in soybean crude oil, as a consequence of phospholipase D inactivation by the fluidized‐bed technique. In addition, fluidized‐bed dryers can be found as part of methods for roasting oilseeds such as flaxseed (Werner, 2008).…”
Section: Introductionmentioning
confidence: 99%